Praksis Literasi Digital dalam Pembelajaran Bahasa Inggris Abad 21 - Floren Agnesia; Ratna Dewanti; Darmahusni Darmahusni (Jurnal Kajian Bahasa, Sastra dan Pengajaran (KIBASP), 2021)
This study aims to determine the praxis of digital literacy carried out in the English learning process at Citra Kasih High School based on the global digital literacy competency framework developed by UNESCO. The method used in this research is descriptive qualitative to describe the practice of digital literacy in learning English at Citra Kasih High School. The results showed that there were seven areas of digital literacy competence that were applied in the English learning process at Citra Kasih High School, namely: 1) hardware and software; 2) information and data literacy; 3) communication and collaboration; 4) digital content creation; 5) security; 6) problem solving; 7) career-related competencies. In conclusion, the indicators of digital literacy skills initiated by UNESCO for the digital community, in general, can be used in the English learning process in particular. The seven digital literacy competency areas applied in learning English at Citra Kasih High School are implemented in preliminary activities, core activities, and closing activities. Keywords: Global Framework, Digital Literacy, Practice, UNESCO